Tantangan dan peluang dalam integrasi lembaga keuangan syariah ke dalam ekonomi digital: strategi transformasi di era revolusi industri 4.0 - Sodiq, Ahmad Fajar (Maliki Interdisciplinary Journal, 2025)
The digital economy transformation has introduced a new paradigm in the global financial industry, including Islamic financial institutions in Indonesia. This research analyzes the challenges and opportunities faced by Islamic financial institutions in integrating into the digital economy. The research method uses a descriptive qualitative approach with literature analysis from various current academic sources. The results show that the digital economy opens up great opportunities through financial technology, operational efficiency, and market reach expansion. However, significant challenges arise in regulatory aspects, technological infrastructure, and cybersecurity. Case studies show that several Islamic financial institutions have successfully adapted through digital product innovation and strategic collaboration. Strategic recommendations include strengthening adaptive regulations, investing in technology infrastructure, and increasing public digital literacy to promote broader Islamic financial inclusion.